2016
DOI: 10.1186/s13053-015-0041-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in Polish patients with BRCA1-dependent ovarian cancer

Abstract: BackgroundTreatment outcomes appear to be better for ovarian cancer (OC) patients carrying the BRCA1/2 germline mutation than for patients with sporadic OC. However, most published data are for North American, British and Jewish populations. There have been very few studies on treatment outcomes in Central and Eastern European patients with OC. The aim of this study was to analyse prognostic factors in Polish patients with BRCA1-dependent OC (BRCA1-OC).MethodsThe records of patients with OC treated with surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Despite the fact that Jacob et al reported 41% prevalence in postmenopausal women, Szatkowski et al found in contrast to our study that 42.4% of ovarian cancer patients are in a postmenopausal status while 57.6% are still menstruating raising the fact that it's important to screen for malignant adnexal masses even in premenopausal women. 22,23 Joung et al stated in his study that the bioavailable ovarian steroid hormone that occurs in diabetes mellitus are also considered potentially carcinogenic conditions for breast, endometrium, and ovaries in women. 24 This is in agreement with our study in which Diabetes Mellitus is found in 32.5% of cases when compared to only 12.5% in control group.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that Jacob et al reported 41% prevalence in postmenopausal women, Szatkowski et al found in contrast to our study that 42.4% of ovarian cancer patients are in a postmenopausal status while 57.6% are still menstruating raising the fact that it's important to screen for malignant adnexal masses even in premenopausal women. 22,23 Joung et al stated in his study that the bioavailable ovarian steroid hormone that occurs in diabetes mellitus are also considered potentially carcinogenic conditions for breast, endometrium, and ovaries in women. 24 This is in agreement with our study in which Diabetes Mellitus is found in 32.5% of cases when compared to only 12.5% in control group.…”
Section: Discussionmentioning
confidence: 99%